2002
DOI: 10.1046/j.1432-1033.2002.03145.x
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone and antichaperone activities of trigger factor

Abstract: Reduced denatured lysozyme tends to aggregate at neutral pH and competition between productive folding and aggregation substantially reduces the efficiency of refolding. Trigger factor, a folding catalyst and chaperone can, depending on the concentration of trigger factor and the solution conditions, cause either a substantial increase (chaperone activity) or a substantial decrease (antichaperone activity) in the recovery of native lysozyme as compared with spontaneous refolding. When trigger factor is working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…To determine the contribution of individual FKBP26 domains to chaperone activity, we tested the different constructs in a well established in vitro chaperone assay using denatured hen egg white lysozyme as a substrate 23,24 Chemically denatured lysozyme aggregated rapidly upon 100-fold dilution, but stoichiometric amounts of FKBP26 efficiently prevented lysozyme aggregation, as no light-scattering signal at 360 nm was observed (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the contribution of individual FKBP26 domains to chaperone activity, we tested the different constructs in a well established in vitro chaperone assay using denatured hen egg white lysozyme as a substrate 23,24 Chemically denatured lysozyme aggregated rapidly upon 100-fold dilution, but stoichiometric amounts of FKBP26 efficiently prevented lysozyme aggregation, as no light-scattering signal at 360 nm was observed (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The higher the concentration of TF, the greater the chance of recapture of substrate intermediates by TF. It was suggested that this binding effect can lead to the arrest of folding (Huang et al, 2002, 2000), so that GFPuv folding was no longer limited by proline isomerization. Thus, it can be concluded that though the limiting-rate role of all the proline residues together in FPs is demonstrated, the role played by each of them is the task of future investigations.…”
Section: Unfolding–refolding Of Fluorescent Proteinsmentioning
confidence: 99%
“…The high cytosolic concentration of TF has recently been linked to a distinct functional role of the chaperone in maintaining newly translated polypeptides in a folding-competent state in the E. coli cytoplasm (35). A distinct antichaperone activity has also been described for TF, however, whereby substoichiometric concentrations of TF lead to increased polypeptide aggregation, whereas high TF/polypeptide ratios can also delay folding as the chaperone maintains polypeptides in a non-native state without promoting their complete refolding (9).…”
mentioning
confidence: 99%